Cooperate or not with knowledge-advantaged ENGO: Motivating supplier environmental responsibility of competitive core enterprises - Meng, Qingchun; Jiang, Yumei; Pan, Jian (Frontiers in Environmental Science, 2022)
Recently, core enterprises are compelled to invest in the environmental responsibility of upstream suppliers, since their brand image and market share will be significantly impacted when suppliers fail to comply with environmental regulations. However, the effectiveness of the core enterprises’ investment efficiency is limited by insufficient environmental knowledge. Although cooperating with the knowledge-advantaged environmental non-governmental organization (ENGO) may be an effective solution, we observe from the recent examples that not all core enterprises are willing to cooperate in a competitive market. Within this context, we develop a theoretical model to investigate whether competitive core enterprises can benefit from cooperating with the knowledge-advantaged ENGO to motivate the supplier’s environmental responsibility. Our results show that cooperation incentivizes core enterprises’ investments in the supplier’s environmental responsibility, which in turn motivates better environmental responsibility of the supplier. However, we illustrate that cooperation is not necessarily the optimal strategy for core enterprises in the duopoly scenario. Specifically, as the knowledge absorption ability increases, a core enterprise may free-ride on another’s investment, shifting its strategic preference from cooperating to not cooperating. In addition, competition may stimulate the core enterprises’ investments and cooperation motivation, thus improving the total environmental effort and supply chain members’ profits. Our findings provide insights into the competitive core enterprises’ strategic choice regarding suppliers’ environmental responsibility management.